Myocardial perfusion scintigraphy in identification and localization of individual coronary lesions - Baškot Branislav; Janković Zoran; Marković Milić; Spaić Rajko (Vojnosanitetski Pregled)
The aim of this study was to evaluate the accuracy of myocardial perfusion scintigraphy with technetium-99m tetrofosmin by single-photon emission computed tomography (SPECT), using one-day protocol in the identification and localization of individual stenosed coronary vessels. Sixty-eight patients with suspected coronary artery disease (CAD) were studied. In thirty of them coronary angiography showed significant stenosis (³50%). Nine patients were with one-vessel disease, 11 were with two-vessel disease, and 10 were with three-vessel disease. All the patients were administered two i.v. injections of 99mTc tetrofosmin, one at peak pharmacologic exercise (1-3 min after i.v. administration of dipiridamol 0.56 mg per kg during 4 min) 370 MBq, and the other 740 MBq at rest 3 hrs after the exercise test (acquisition was obtained 15-30 min after injections for both studies). Overall sensitivity, specificity, and diagnostic accuracy in the identification of individual stenosed coronary vessels were 90%, 86%, and 88%, respectively. Sensitivity, specificity, and accuracy in each of the individual vascular territories were not significantly different: LAD (96% 64%, and 75%), ACx (73%, 100%, and 94%), RCA (95%, 93%, and 94%). The results of this study demonstrated one-day 99mTc-tetrofosmin SPECT scintigraphy to be suitable and accurate technique for the identification and localization of individual stenosed coronary vessels, as well as a highly sensitive method in the recognition of one- and multiple-vessel diseases of coronary arteries.